Analysis of Students’ Digital Accessibility in Terms of Use of Technology and Obstacles Faced in Learning Biology - Ida Yayu Nurul Hizqiyah; Ari Widodo; Siti Sriyati (Scientiae Educatia: Jurnal Pendidikan Sains, 2022)
The need for labor in the future has more complex criteria than what is needed today. The increasing complexity of these criteria is due to technological advances which are increasingly shifting the position of humans at work. Technology has advantages and stability and can predict the results obtained. So it is essential for everyone to prepare for the increasingly fierce competition in the world of work. One of the efforts made is to familiarize students with technology at school. However, this needs to be supported by the availability of facilities and infrastructure as well as the ability of students to adapt. So this study aims to capture the digital accessibility of students in terms of the factors and obstacles they face in using technology. These data were obtained by applying the survey method to 41 students at SMA Bandung City. In this study, the data were analyzed quantitatively and represented in the form of diagrams. The results of data analysis show that students have adequate digital accessibility. This is indicated by their readiness and independence in learning technology as an additional learning resource. However, the biggest obstacle students face is the lack of stability in the internet network. So that it interferes with the learning process.